Effects of ACEI/ARB or CCB use on atrial fibrillation in hypertensive patients following permanent pacemaker implantation - Liu, Zhijie; Bian, Ning; Wu, Shaorong; Cao, Yantao; Su, Yiting; Li, Wenying; Li, Hairui; Lan, Xianwu; Jiang, Can; Fan, Yiming; Guo, Jun; Chen, Dongdong (Frontiers in Cardiovascular Medicine, 2023)
Aims: Permanent pacemaker implantation (PPI) combined with hypertension leads to a higher risk of new-onset atrial fibrillation (NOAF) for patients. Hence, it is essential to study how to reduce this risk. Currently, the effects of the two common anti-hypertensive drugs, angiotensin-converting enzyme inhibitors (ACEI)/angiotensin receptor blockers (ARB) and calcium channel blockers (CCB), on the risk of NOAF for such patients remain unknown. This study aimed to investigate this association. Methods: This single-center retrospective study included hypertensive patients with PPI and without prior history of AF/atrial flutter, heart valve disease, hyperthyroidism, etc. Patients were classified into ACEI/ARB group and CCB group based on their exposure drug information. The primary outcome was NOAF events that occurred within 12 months after PPI. The secondary efficacy assessments were the changes from baseline to follow-up in blood pressure and transthoracic echocardiography (TTE) parameters. A multivariate logistic regression model was used to verify our aim. Results: A total of 69 patients were finally included (51 on ACEI/ARB and 18 on CCB). Both univariate analysis (odds ratio [OR] 0.241, 95% confidence interval [CI] 0.078-0.745) and multivariate analysis (OR 0.246, 95% CI 0.077-0.792) demonstrated that ACEI/ARB were associated with a lower risk of NOAF compared to CCB. The mean reduction in left atrial diameter (LAD) from baseline was greater in ACEI/ARB group than in CCB group (p=0.034). There was no statistical difference between groups in blood pressure and other TTE parameters after treatment. Conclusion: For patients with PPI combined with hypertension, ACEI/ARB may be superior to CCB in selecting anti-hypertensive drugs, as ACEI/ARB further reduces the risk of NOAF. One reason for this may be that ACEI/ARB improves left atrial remodelling such as LAD better.